Effect of Dissolved Oxygen, Sodium Bisulfite, and Oxygen Scavengers on Methane Hydrate Inhibition - Alef, Khalid; Iglauer, Stefan; Barifcani, Ahmed (American Chemical Society, 2018)
© 2018 American Chemical Society. Numerous chemical additives are added to monoethylene glycol (MEG) injection streams to maintain and protect assets as well as to ensure steady production of hydrocarbons. Oxygen scavengers are injected for the purpose of lowering dissolved oxygen to levels that do not pose the risk of corrosion. In this study, the effect of dissolved oxygen and some oxygen scavengers on gas hydrate inhibition was investigated. Results reveal that high levels of dissolved oxygen may promote the formation of hydrates due to the reaction of dissolved oxygen with impurity components such as iron carbonate that may exist in the MEG solution, thus decreasing overall MEG quality. Sodium bisulfite had negligible effect on hydrate inhibition at low concentrations but showed greater inhibition performance at higher concentrations due to the electrostatic attraction between ions and water molecules. A proprietary oxygen scavenger showed hydrate promotion effect, which suggests that proprietary chemical additives should undergo extensive compatibility and risk analysis. An erythorbic acid-based oxygen scavenger showed minor inhibition performance albeit at small concentration, possibly due to hydrogen bonding between hydroxyl groups of its components with water molecules.